The Use of Wayfinding Apps by Deafblind Travelers in an Urban Environment: Insights From Focus Groups - Parker, Amy T.; Swobodzinski, Martin; Brown-Ogilvie, Tara; Beresheim-Kools, Jenna (Frontiers in Education, 2020)
This brief report explores qualitative themes from focus groups with nine individuals who are Deafblind regarding their use of wayfinding apps to support orientation and mobility in an urban environment. Culturally responsive approaches to the design of the focus groups integrated the partnership with Deafblind communication facilitators and ProTactile approaches to solicit naturalistic inquiry on the experiences and preferences of Deafblind travelers. Thematic emergences suggest that participants benefit from various wayfinding apps for orientation and mobility in a densely populated city but they desire greater functionality, consistency of access, equity, and recognition of the unique travel demands faced by Deafblind travelers.